AN ANALYSIS OF INDONESIAN TRANSLATION OF ENGLISH SONG LYRICS IN HOT CHORD MONTHLY MAGAZINE - Erfan Nurmansyah, - (2008)
The present study was conducted under the title "An Analysis of Indonesian Translation of English Song Lyrics in HOT CHORD Monthly Magazine". The aim of this study is to investigate the procedures that were used in the Indonesian translation of the English songs lyrics in Hot Chord magazine. This study applies a qualitative approach that is descriptive in nature. By using this research the data found were described, analyzed, and interpreted without controlling or giving any treatment to the variable. This study also uses descriptive quantification to examine tendencies. The result of the study shows that the most frequent translation procedure used by the translator was Literal translation (52,5%). Other procedures that were used by the translator were Transference (5%), Modulation (12,5%), Reduction (12,5%), Couplets (12,5%), and Addition (5%).